Analysis Of Connectivity Spending, Capital Expenditure And Fiscal Independence On The Pace Of GDP - Ciptawaty, Ukhti; Marselina, Marselina; Amalkhan, Gwen Adhitya (Equity: Jurnal Ekonomi, 2025)
This study analysed the issue of the quality of regional spending, by analyzing the influence of Connectivity Spending, Capital Expenditure and Fiscal Independence on the GDP growth rate in Regencies/Cities throughout Lampung Province in the period 2018 to 2022. The results of the analysis indicated that the Connectivity Expenditure variable had a positive and significant influence on the GDP rate, meaning that every 1% increase in connectivity spending could increase the GDP growth rate by 0.26%. Meanwhile, Capital Expenditure had a negative impact or suppresses the GDP rate. It marked the allocation of the capital expenditure budget for asset acquisition was less effective in supporting economic growth and development between regions. Likewise, Fiscal Independence had no significant effect on the pace of GDP. This condition reflected the region's large dependence on central transfers. Using the Vector Autoregression (VAR) found that all variables affect GDP with a lag of 1 year after meaning that three variables could affect the rate of GDP after 1 year of implementation. The results of this study overviewed the importance of selecting efficient types of Capital Expenditure and Connectivity Expenditure which had an impact on economic growth (spending better), as well as the importance of increasing regional fiscal capacity through PAD optimization to support regional financing and sustainable regional economic growth.